Lipopolysaccharide from Rhodobacter sphaeroides Attenuates Microglia-Mediated Inflammation and Phagocytosis and Directs Regulatory T Cell Response - Sagar Gaikwad; Reena Agrawal-Rajput (Hindawi Limited, 2015)
Microglia activation and neuroinflammation are key events during the progression of neurodegenerative disorders. Microglia exhibits toll-like receptors (TLRs), with predominant expression of TLR4, inducing aberrant neuroinflammation and exacerbated neurotoxicity. Studies suggest that microglia initiate infiltration of T cells into the brain that critically influence disease conditions. We report that LPS-Rs, through TLR4 antagonism, significantly inhibit TLR4 mediated inflammatory molecules like IL-1β, IL-6, TNF-α, COX-2, iNOS, and NO. LPS-Rs regulates JNK/p38 MAPKs and p65-NF-κB signaling pathways, which we report as indispensible for LPS induced neuroinflammation. LPS-Rs mitigates microglial phagocytic activity and we are first to report regulatory role of LPS-Rs which blocked microglia mediated inflammation and apoptotic cell death. LPS-Rs significantly inhibits expression of costimulatory molecules CD80, CD86, and CD40. Chemokine receptor, CCR5, and T cell recruitment chemokines, MIP-1α and CCL5, were negatively regulated by LPS-Rs. Furthermore, LPS-Rs significantly inhibited lymphocyte proliferation with skewed regulatory T (Treg) cell response as evidenced by increased FOXP3, IL-10, and TGF-β. Additionally, LPS-Rs serves to induce coordinated immunosuppressive response and confer tolerogenic potential to activated microglia extending neurosupportive microenvironment. TLR4 antagonism can be a strategy providing neuroprotection through regulation of microglia as well as the T cells.